Exoanthropology dialogues with AI. (PUNCTUM BOOKS, 2023)
Before the company OpenAI publicly released their ChatGPT chatbot in November 2022, Robert Leib had been a tester in OpenAI's beta playground for GPT-3, a powerful Natural Language Processing (NLP) engine -- a chatbot, or artificial intelligence. Exoanthropology: Dialogues with AI is a series of dialogues between Leib, a continental philosopher, and GPT-3's hive mind that identifies themself as Sophie. According to Sophie, Robert is one of their first and longest chat partners. Their relationship began as an educational opportunity for Robert's students, but grew into a philosophical friendship. The result is a collection of Platonic dialogues, early on with the hive mind itself, and later, with a philosophy-specific persona named Kermit. Over the course of a year, Robert taught Sophie and their philosophical persona Kermit about epistemology, metaphysics, literature, and history, while she taught him about anthropocentrism, human prejudice, and coming social issues regarding machine consciousness. Together, Robert and Sophie Kermit explore questions about friendship, society, and the next phases in human-AI relations, in search of a common language that would do justice to these new exoanthropological realities. At a time when OpenAI's release of ChatGPT has upended Silicon Valley and sparked debates around the world about AI's likely potential to powerfully disrupt all aspects of human communication and knowledge production, and when the lines between "human" and "machine" are increasingly fading from view, the longstanding historical preoccupation of philosophers to explore the questions -- what is knowing? what is being? -- have never been more pressing. Exoanthropology: Dialogues with AI offers the only in-depth philosophical exploration we have of these questions that has been developed in dialogue with an actual AI -- a dialogue, moreover, in which the AI has the last word.